Polyamide resin composition
By adding polyolefin-based graft copolymers containing aromatic ring polymers, compatibilizers and non-fibrous fillers to the polyamide resin, the problem of mechanical strength reduction caused by the use of polytetrafluoroethylene in the polyamide resin is solved, and a composition with excellent sliding characteristics, heat resistance and mechanical characteristics is achieved.
Patent Information
- Application Number
- CN202411304753.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-22
- Filing Date
- 2024-09-19
- Publication Date
- 2025-03-25
AI Technical Summary
When polytetrafluoroethylene is used as the fluorine resin, the mechanical strength of the polyamide resin is reduced, and the change in the melt viscosity of the polyamide resin and the polyolefin resin affects the mechanical properties and sliding properties.
The polyamide resin composition with polyolefin-based graft copolymers, compatibilizers and non-fibrous filler materials having aromatic ring polymers in the side chains is used to improve the sliding characteristics and heat resistance through melt kneading technology.
A polyamide resin composition with excellent sliding characteristics, heat resistance and mechanical characteristics is achieved, and deterioration of the polyamide resin and a decrease in mechanical strength are avoided.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention relates to a polyamide resin composition. Background Art
[0002] Polyamide resins have excellent sliding properties, molding processability, mechanical properties, chemical resistance, etc. Polyamide resins have been widely used as component materials for industrial materials, automobiles, electrical and electronic products, and industrial applications.
[0003] In recent years, the use of resins for metal parts has been progressing in the automotive field, electrical and electronic fields, etc. In particular, in the automotive field, from the perspectives of weight reduction, cost reduction, and rationalization of assembly processes to improve fuel economy, molding materials with better sliding properties and heat resistance, and better mechanical properties such as strength and elastic modulus are required.
[0004] As a method for further improving the sliding properties of polyamide resins, there is known a technique of blending and kneading a solid lubricant such as a fluorine-containing resin, graphite, or molybdenum disulfide into a polyamide resin.
[0005] For example, Patent Documents 2 to 4 disclose polyamide resin compositions in which a fluorine-containing resin is blended into a polyamide resin to improve sliding properties.
[0006] Patent Document 1 discloses a sliding member for a power transmission guide obtained by dispersing a polyolefin resin in a polyamide resin.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2016-117842
[0010] Patent Document 2: International Publication No. WO2013 / 047625
[0011] Patent Document 3: Japanese Patent Application Publication No. 2011-84679
[0012] Patent Document 4: Japanese Patent Application Publication No. 2012-102189 Summary of the invention
[0013] Problems to be solved by the invention
[0014] Regarding the technology of blending a fluorine-containing resin into a polyamide resin as disclosed in Patent Documents 2 to 4, for example, polytetrafluoroethylene is used as the fluorine-containing resin to be blended.
[0015] However, when polytetrafluoroethylene is used as the fluorine-containing resin, melt kneading is required at a temperature above the melting point of polytetrafluoroethylene and under high shear conditions in order to finely disperse the polytetrafluoroethylene. As a result of the melt kneading, there is a problem that the polyamide resin deteriorates and the mechanical strength decreases.
[0016] In addition, regarding the technology of blending a polyolefin resin into a polyamide resin as disclosed in Patent Document 1, the melt viscosities of the polyamide resin and the polyolefin resin are different, and sometimes the melt viscosities of the polyamide resin and the polyolefin resin also vary greatly depending on the shear rate applied during production. As a result, there is a problem that the morphology of the polyolefin resin has a great influence on the mechanical properties and sliding properties.
[0017] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a polyamide resin composition having excellent sliding properties, heat resistance, and mechanical properties.
[0018] Means used to solve problems
[0019] The present invention includes the following aspects.
[0020] [1] A polyamide resin composition, characterized in that the polyamide resin composition contains:
[0021] (A) Polyamide resin,
[0022] (B) a polyolefin graft copolymer having an aromatic ring-containing polymer in a side chain,
[0023] (C) Compatibilizer, and
[0024] (D) Non-fibrous filling materials.
[0025] [2] The polyamide resin composition according to [1], wherein the (C) compatibilizer has an olefin skeleton and / or an aromatic ring skeleton.
[0026] [3] The polyamide resin composition according to [1] or [2], wherein the content of the (B) polyolefin graft copolymer is 1 to 15 parts by mass based on 100 parts by mass of the (A) polyamide resin,
[0027] The content of the (C) compatibilizer is 0.01 to 15 parts by mass relative to 100 parts by mass of the (A) polyamide resin.
[0028] The content of the (D) non-fibrous filler is 1 to 150 parts by mass based on 100 parts by mass of the (A) polyamide resin.
[0029] [4] The polyamide resin composition according to any one of [1] to [3], wherein the (C) compatibilizer has affinity for an olefin skeleton.
[0030] [5] The polyamide resin composition according to any one of [1] to [4], wherein the (C) compatibilizer has an affinity for an aromatic ring.
[0031] [6] The polyamide resin composition according to [1] to [5], wherein the (C) compatibilizer has a reactive functional group that reacts with the (A) polyamide resin.
[0032] [7] The polyamide resin composition according to any one of [1] to [6], wherein the (B) polyolefin-based graft copolymer has polyethylene in its main chain.
[0033] [8] The polyamide resin composition according to any one of [1] to [7], wherein the (C) compatibilizer contains a structural unit derived from a carboxylic acid anhydride.
[0034] [9] The polyamide resin composition according to any one of [1] to [8], wherein the weight average particle size and / or weight average major axis of the (D) non-fibrous filler is 0.01 μm or more and 300 μm or less.
[0035]
[10] The polyamide resin composition according to any one of [1] to [9], wherein the (C) compatibilizer has an amide bond in a side chain.
[0036]
[11] The polyamide resin composition according to any one of [1] to
[10] , further comprising 0.01 to 5 parts by mass of a copper compound relative to 100 parts by mass of the (A) polyamide resin,
[0037] The present invention further comprises 0.05 to 5 parts by mass of a halide of at least one metal selected from the group consisting of alkali metals and alkaline earth metals, based on 100 parts by mass of the (A) polyamide resin.
[0038]
[12] A method for producing a polyamide resin composition, characterized in that (A) a polyamide resin, (B) a polyolefin graft copolymer having an aromatic ring-containing polymer in a side chain, and (C) a compatibilizer are melt-kneaded.
[0039]
[13] A molded article obtained by molding the polyamide resin composition according to any one of [1] to
[11] .
[0040]
[14] A sliding member, comprising the polyamide resin composition according to any one of [1] to
[11] .
[0041] Effects of the Invention
[0042] According to the present invention, a polyamide resin composition having excellent sliding properties and heat resistance and excellent mechanical properties such as strength and elastic modulus can be obtained. DETAILED DESCRIPTION
[0043] Hereinafter, a mode for carrying out the present invention (hereinafter referred to as “this embodiment”) will be described in detail.
[0044] The following embodiments are examples for explaining the present invention, and are not intended to limit the present invention to the following contents. The present invention can be implemented by being appropriately modified within the scope of the gist of the invention.
[0045] In addition, in this specification, "polyamide" refers to a polymer having an amide (-NHCO-) group in the main chain.
[0046] Regarding the numerical range, "A or more and B or less" may be expressed as "A to B". For example, when it is expressed as "1 part by mass to 10 parts by mass", it means a numerical range from 1 part by mass to 10 parts by mass and including the lower limit (1 part by mass) and the upper limit (10 parts by mass), that is, "1 part by mass or more and 10 parts by mass or less".
[0047] <Polyamide resin composition>
[0048] The polyamide resin composition of the present embodiment is a polyamide resin composition containing (A) a polyamide resin (hereinafter sometimes referred to as the (A) component), (B) a polyolefin graft copolymer having an aromatic ring-containing polymer in a side chain (hereinafter sometimes referred to as the (B) component), (C) a compatibilizer (hereinafter sometimes referred to as the (C) component), and (D) a non-fibrous filler.
[0049] Hereinafter, each component of the polyamide resin composition according to the present embodiment will be described.
[0050] ((A) Polyamide resin)
[0051] The polyamide resin (A) in the present embodiment is not limited to the following, and examples thereof include (a-1) polyamides obtained by ring-opening polymerization of lactams, (a-2) polyamides obtained by self-condensation of ω-aminocarboxylic acids, (a-3) polyamides obtained by condensation of diamines and dicarboxylic acids, and copolymers thereof.
[0052] As the (A) polyamide resin, one type of the polyamide resin may be used alone, or two or more types thereof may be used as a mixture.
[0053] Here, examples of the lactam used for producing the polyamide (a-1) include pyrrolidone, caprolactam, undecanolactam, and lauryl lactam, but are not limited thereto.
[0054] Examples of the ω-aminocarboxylic acid used for producing the polyamide (a-2) include, but are not limited to, ω-amino fatty acids that are ring-opening compounds of the lactams generated by water.
[0055] Furthermore, as the above-mentioned lactam or the above-mentioned ω-aminocarboxylic acid, two or more monomers may be used in combination for condensation.
[0056] Examples of the diamine (monomer) used for producing the polyamide (a-3) include, but are not limited to, linear aliphatic diamines, branched aliphatic diamines, alicyclic diamines, and aromatic diamines.
[0057] Examples of the linear aliphatic diamine include hexamethylenediamine and pentamethylenediamine, but are not limited thereto.
[0058] Examples of the branched aliphatic diamine include 2-methylpentanediamine and 2-ethylhexamethylenediamine, but are not limited thereto.
[0059] Examples of the alicyclic diamine include cyclohexanediamine, cyclopentanediamine, cyclooctanediamine, and the like, but the alicyclic diamine is not limited thereto.
[0060] Examples of the aromatic diamine include p-phenylenediamine and m-phenylenediamine, but are not limited thereto.
[0061] Examples of the dicarboxylic acid (monomer) used for producing the polyamide (a-3) include, but are not limited to, aliphatic dicarboxylic acids, alicyclic dicarboxylic acids, and aromatic dicarboxylic acids.
[0062] Examples of the aliphatic dicarboxylic acid include adipic acid, pimelic acid, sebacic acid, and the like, but the aliphatic dicarboxylic acid is not limited thereto.
[0063] Examples of the alicyclic dicarboxylic acid include cyclohexanedicarboxylic acid, but the alicyclic dicarboxylic acid is not limited thereto.
[0064] Examples of the aromatic dicarboxylic acid include phthalic acid and isophthalic acid, but are not limited thereto.
[0065] In addition, the diamine and dicarboxylic acid as the above-mentioned monomers may be condensed individually or in combination of two or more.
[0066] Examples of the polyamide of the component (A) include polyamide 4 (poly-α-pyrrolidone), polyamide 6 (polycaproamide), polyamide 11 (polyundecanamide), polyamide 12 (polydodecamide), polyamide 46 (polybutylene adipamide), polyamide 66 (polyhexamethylene adipamide), polyamide 610 (polyhexamethylene sebacamide), polyamide 612 (polyhexamethylene dodecanoamide), polyamide 6T (polyhexamethylene terephthalamide), polyamide 9T (polynonamethylene terephthalamide), polyamide 6I (polyhexamethylene isophthalamide), polyamide 2Me5T (poly-2-methylpentamethylene terephthalamide (hereinafter, methyl group may be referred to as Me)), polyamide MXD6 (polymeta-phenylene adipamide), polyamide PXD12 (polyp-phenylene dodecanoamide), and copolymer polyamides containing at least one of these polyamides as a constituent component, but are not limited thereto.
[0067] As the polyamide resin (A), from the viewpoint of improving sliding properties, polyamide resins mainly composed of polyamide 66, polyamide 46, polyamide 4T, polyamide 6T, polyamide 9T, and polyamide 6 are preferred. It should be noted that the "main component" referred to herein refers to a polyamide resin component having a content ratio of 50% by mass or more relative to the total mass of the polyamide resin (A).
[0068] In terms of improving heat resistance, the polyamide resin (A) is preferably a polyamide resin containing polyamide 66, polyamide 46, polyamide 4T, polyamide 6T, polyamide 9T, and polyamide PXD12 as a main component, and more preferably a polyamide resin containing polyamide 66 as a main component.
[0069] The sulfuric acid relative viscosity of the polyamide resin (A) is preferably 2.0 or more, more preferably 2.1 or more, further preferably 2.3 or more, and particularly preferably 3.2 or more.
[0070] The sulfuric acid relative viscosity of the polyamide resin (A) is preferably 4.5 or less, more preferably 4.4 or less, and particularly preferably 4.3 or less.
[0071] When the sulfuric acid relative viscosity of the polyamide resin (A) is 2.0 or more, a polyamide resin composition having better mechanical properties tends to be obtained. When the sulfuric acid relative viscosity is 4.5 or less, a polyamide resin composition having better fluidity and processability tends to be obtained.
[0072] The sulfuric acid relative viscosity of the polyamide resin (A) can be measured by the method described in JIS-K6920 described in Examples below.
[0073] In the polyamide resin composition of the present embodiment, as the component (A), a known polyamide resin may be used, or a commercially available product may be used.
[0074] ((B) Polyolefin-based graft copolymer having an aromatic ring-containing polymer in a side chain)
[0075] The polyamide resin composition of the present embodiment contains (B) a polyolefin graft copolymer having an aromatic ring-containing polymer in a side chain. The (B) polyolefin graft copolymer having an aromatic ring-containing polymer in a side chain is not particularly limited as long as it is a polyolefin graft copolymer having an aromatic group in a side chain.
[0076] By containing the (B) component, the sliding properties of the obtained polyamide resin composition are improved.
[0077] The component (B) is preferably (b-1) an olefin graft copolymer having polystyrene in the aromatic ring, and more preferably (b-2) an olefin graft copolymer having polyethylene in the main chain. The side chain is not limited to polystyrene, and may be a vinyl copolymer or the like.
[0078] Here, the method for producing the component (B) is not particularly limited, and the component can be easily produced by a known radical reaction.
[0079] As a method for preparing the component (B), for example, there is a method in which a radical catalyst is added to monomers constituting an olefin polymer component including polyethylene and monomers constituting a vinyl polymer, followed by kneading to perform grafting.
[0080] Another method is to add a radical catalyst such as a peroxide to an olefin polymer component or a vinyl polymer component to generate radicals, and then melt-knead the generated radicals with another polymer component to carry out grafting.
[0081] The component (B) is a graft copolymer having a polyolefin as a main chain and an aromatic ring-containing polymer in a side chain. This can prevent the component (B) from falling off from the polyamide resin, and can obtain a polyamide resin composition having excellent sliding properties, especially wear resistance.
[0082] The polyamide resin composition of the present embodiment preferably contains at least 50% by mass or more of polyethylene based on 100% by mass of the component (B).
[0083] The ratio of (b1) olefin polymer to (b2) vinyl copolymer constituting the component (B) is preferably b1:b2=80:20 to 20:80 (mass ratio), and particularly preferably b1:b2=60:40 to 40:60.
[0084] By satisfying the above ratio, the sliding properties of the obtained polyamide resin composition can be improved.
[0085] The (b2) vinyl-based copolymer exhibits high rigidity due to a high glass transition temperature that is a characteristic of the aromatic ring.
[0086] In addition, the vinyl copolymer can prevent the following phenomenon: the temperature of the sliding surface increases due to the friction force (frictional heat) applied to the sliding surface of the vinyl copolymer, so that the (B) component is easily sintered and welded with the sliding part such as the meshing part of the counterpart material or the self material on the sliding surface. As a result, the sliding characteristics can be maintained for a long time, and in particular, the wear resistance is improved.
[0087] The content of the component (B) in the polyamide resin composition of the present embodiment is preferably 1 to 15 parts by mass, more preferably 2 to 12 parts by mass, and even more preferably 3 to 10 parts by mass, relative to 100 parts by mass of the polyamide resin (A).
[0088] When the content of the component (B) is greater than or equal to the lower limit (1 part by mass), the sliding properties of the obtained polyamide resin composition can be effectively exerted. On the other hand, when the content of the component (B) is less than or equal to the upper limit (15 parts by mass), the wear resistance and mechanical properties of the obtained polyamide resin composition are improved.
[0089] As the component (B) in the polyamide resin composition of the present embodiment, any known component may be used as long as it is a polyolefin-based graft copolymer having an aromatic group in a side chain, and a commercially available product may also be used.
[0090] ((C) Compatibilizer)
[0091] The polyamide resin composition in the present embodiment contains (C) a compatibilizer. The (C) compatibilizer is not limited to the following substances, and is not particularly limited as long as it is a compound that can improve the compatibility of the compound containing an olefin skeleton and / or an aromatic ring skeleton with the polyamide resin from the viewpoint of better sliding properties, mechanical properties, heat resistance, long-term heat resistance, moldability, processability, etc.
[0092] By adding (C) a compatibilizer for improving the compatibility between the (A) polyamide resin and the (B) polyolefin graft copolymer having an aromatic ring-containing polymer in the side chain, the sliding properties, mechanical properties, heat resistance, long-term heat resistance, moldability and processability of the polyamide resin composition in this embodiment are further improved.
[0093] In addition, the component (C) preferably contains an olefin skeleton and / or an aromatic ring skeleton. In addition, as the component (C), as a compound capable of improving compatibility with the polyamide resin, for example, at least one compound selected from compounds having an amide bond such as polyamide and / or their copolymers, compounds having a reactive functional group capable of reacting with an end group and / or a main chain amide group of the polyamide resin, etc. is preferably used, but the invention is not limited thereto.
[0094] As the compound containing an olefin skeleton, for example, at least one compound selected from low-density polyethylene (LDPE), high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), ultra-high molecular weight polyethylene (UHMWPE), ultra-low density polyethylene (VLDPE) obtained by the action of a metallocene catalyst, polyethylene, α-olefin or diene, styrene / butadiene / styrene block copolymer (SBS), styrene / ethylene-butylene / styrene block copolymer (SEBS) as a hydrogenation product thereof, styrene / butadiene copolymer (SBR), styrene / ethylene / butylene copolymer (HSBR) as a hydrogenation product thereof, styrene / isoprene / styrene block copolymer (SIS), styrene / ethylene-propylene / styrene block copolymer (SEPS) as a hydrogenation product thereof, etc. can be used, but it is not limited thereto. It should be noted that in this specification, the olefin skeleton is defined as a compound composed only of carbon atoms and hydrogen atoms.
[0095] As the compound containing an aromatic ring skeleton, for example, at least one selected from low-density polyethylene (LDPE), high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), ultra-low-density polyethylene (VLDPE) obtained by the action of a metallocene catalyst, polyethylene, α-olefin or diene, polystyrene having an aromatic ring skeleton, polyphenylene ether, modified polyphenylene ether, styrene / butadiene / styrene block copolymer (SBS), styrene / ethylene-butylene / styrene block copolymer (SEBS) as a hydrogenation product thereof, styrene / butadiene copolymer (SBR), styrene / ethylene / butylene copolymer (HSBR) as a hydrogenation product thereof, styrene / isoprene / styrene block copolymer (SIS), styrene / ethylene-propylene / styrene block copolymer (SEPS) as a hydrogenation product thereof, etc. can be used, but it is not limited thereto.
[0096] Examples of the α-olefin include ethylene, propylene, 1-butene, 1-octene, butadiene, and the like, but the α-olefin is not limited thereto.
[0097] Examples of the diene include diene homopolymers and copolymers, but are not limited thereto.
[0098] The (C) compatibilizer preferably has an olefin skeleton and / or an aromatic ring skeleton, but is not limited thereto. In addition, the (C) compatibilizer preferably has an olefin skeleton and / or an aromatic ring skeleton in the main chain, more preferably has an olefin skeleton and / or a styrene skeleton in the main chain of the (C) component, and particularly preferably has at least an olefin skeleton in the main chain of the (C) component.
[0099] As a compound capable of improving compatibility with the above-mentioned polyamide resin, for example, at least one of a compound having an amide bond selected from polyamide, a copolymer containing polyamide, a combination thereof, and a compound having a reactive functional group capable of reacting with an amide group in the terminal group and / or the main chain of the polyamide resin can be used, but it is not limited thereto.
[0100] Examples of the reactive functional group capable of reacting with the terminal group of the polyamide resin and / or the amide group in the main chain include a carboxyl group, an acid anhydride group, an epoxy group, Azoline, amino, isocyanate, maleic anhydride, itaconic anhydride, citraconic anhydride, allyl succinic anhydride, 4-cyclohexene-1,2-dicarboxylic anhydride, 4-methyl-4-cyclohexene-1,2-dicarboxylic anhydride, bicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride, methylbicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride, etc.
[0101] There is no particular limitation on the method for introducing the reactive functional group, and examples thereof include a method of reacting a compound having the reactive functional group in the process of manufacturing the polymer, a method of mixing the polymer pellets with a compound having the reactive functional group and reacting them by kneading them using an extruder, etc.
[0102] The (C) compatibilizer is more preferably a compound having an amide bond such as polyamide and / or a copolymer thereof; or a compound having a reactive functional group having a structural unit derived from a carboxylic anhydride, but is not limited thereto.
[0103] It is further preferred that the (C) compatibilizer is a compound having an amide bond and / or a compound having a structural unit derived from maleic acid.
[0104] In particular, it is preferred that the (C) compatibilizer is a compound having an amide bond.
[0105] Most preferably, the (C) compatibilizer is a compound having an amide bond in a side chain.
[0106] In addition, from the viewpoint of more excellent sliding properties, mechanical properties, heat resistance, long-term heat resistance, moldability, processability, etc., the above-mentioned (C) compatibilizer is preferably: a compound having an olefin skeleton and / or an aromatic ring skeleton; an amide bond such as polyamide and / or a copolymer thereof; or a reactive functional group containing a structural unit derived from a carboxylic anhydride, but is not limited thereto.
[0107] Furthermore, the (C) compatibilizer is more preferably: a compound having an olefin skeleton and / or an aromatic ring skeleton in the main chain; or a compound having an amide bond and / or containing a structural unit derived from maleic acid.
[0108] Furthermore, the (C) compatibilizer particularly preferably has only an olefin skeleton or a styrene skeleton in the main chain and an amide bond in the side chain, and most preferably has an olefin skeleton in the main chain and an amide bond in the side chain.
[0109] As described above, the (C) compatibilizer is most preferably a graft copolymer having an olefin skeleton in the main chain and an amide bond in the side chain from the viewpoint of better sliding properties, mechanical properties, heat resistance, long-term heat resistance, moldability, processability, etc.
[0110] In this case, it can be obtained by reaction of the residue of the unsaturated monomer in the main chain part with the terminal of the skeleton having an amide bond, but the present invention is not limited thereto.
[0111] As an unsaturated monomer, an unsaturated epoxide, an unsaturated carboxylic acid anhydride, the salt or ester of an unsaturated carboxylic acid, the vinyl ester of a saturated carboxylic acid, etc. are mentioned, for example.
[0112] Examples of the unsaturated carboxylic anhydride include maleic anhydride, itaconic anhydride, citraconic anhydride, allylsuccinic anhydride, 4-cyclohexene-1,2-dicarboxylic anhydride, 4-methyl-4-cyclohexene-1,2-dicarboxylic anhydride, bicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride, and methylbicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride, but are not limited thereto.
[0113] Examples of the salt or ester of the unsaturated carboxylic acid include, but are not limited to, alkyl (methacrylic acid) acrylate (methyl acrylate) and the like.
[0114] Examples of the vinyl ester of the saturated carboxylic acid include vinyl acetate, but are not limited thereto.
[0115] In the polyamide resin composition of the present embodiment, since at least one of the above-mentioned (B) component and the above-mentioned (C) component is a graft copolymer having an olefin skeleton in the main chain and an amide bond in the side chain, it is possible to exert innovative effects not found in the known technologies in terms of sliding properties, mechanical properties, heat resistance, long-term heat resistance, moldability, processability, etc.
[0116] From the viewpoint of further improving the compatibility of the olefin skeleton and / or the aromatic ring skeleton with the (A) polyamide resin, it is particularly preferred that both the (B) component and the (C) component are graft copolymers, but the present invention is not limited thereto.
[0117] In addition, in the polyamide resin composition of this embodiment, the above-mentioned (C) component can use a well-known thing, and can also use a commercial item.
[0118] The above-mentioned (C) component is not particularly limited and can also be produced using the following masterbatch, which is prepared by preliminarily melt-kneading at least one compound selected from compounds having a reactive functional group that can react with the terminal group of the polyamide resin and / or the amide group of the main chain with a polymer having an olefin skeleton and / or an aromatic ring skeleton (for example, a thermoplastic resin such as a polyamide resin).
[0119] The above-mentioned (C) component can be produced, for example, using the following masterbatch, which is prepared by preliminarily melt-kneading a compound having at least one selected from the group consisting of a terminal group and / or a reactive functional group capable of reacting with an amide group in the main chain of the polyamide resin (A) and a compound having at least one selected from the group consisting of an olefin skeleton and an aromatic ring skeleton (for example, a thermoplastic resin such as a polyamide resin).
[0120] Alternatively, the component (C) may be, for example, a masterbatch prepared by melt-kneading a precursor of a graft copolymer having an unsaturated monomer in its skeleton and a thermoplastic resin having a reactive functional group reactive with the unsaturated monomer.
[0121] Alternatively, the component (C) can also be obtained by adding a graft copolymer precursor having an unsaturated monomer in its skeleton when melt-kneading the component (A) and the component (B) during the production of the polyamide resin composition of the present embodiment, and reacting the graft copolymer precursor with the component (A).
[0122] That is, the polyamide resin composition containing the components (A), (B) and (C) can be obtained by melt-kneading a composition containing the components (A) and (B) using an extruder or the like.
[0123] The content of the component (C) in the polyamide resin composition of the present embodiment is preferably 0.01 to 15 parts by mass, more preferably 0.05 to 15 parts by mass, further preferably 0.1 to 12 parts by mass, and particularly preferably 0.2 to 10 parts by mass, relative to 100 parts by mass of the polyamide resin (A).
[0124] When the content of the component (C) is at least the lower limit (0.01 parts by mass), sliding properties, moldability, processability, etc. are effectively exhibited, and when the content of the component (C) is at most the upper limit (15 parts by mass), sliding properties, mechanical properties, heat resistance, long-term heat resistance, moldability, processability, etc. are improved.
[0125] ((D) Non-fibrous filling material)
[0126] The polyamide resin composition in the present embodiment contains (D) a non-fibrous filler. Examples of the (D) non-fibrous filler include, but are not limited to, wollastonite, calcium carbonate, talc, kaolin, mica, glass flakes, hydrotalcite, zinc carbonate, calcium hydrogen phosphate, zeolite, boehmite, magnesium oxide, calcium silicate, sodium aluminosilicate, magnesium silicate, Ketjen black, acetylene black, furnace black, carbon nanotubes, graphite, brass, copper, silver, aluminum, nickel, iron, calcium fluoride, montmorillonite, swelling fluorine mica, apatite, milled fiber, boron nitride, and the like.
[0127] These (D) non-fibrous fillers may be used alone or in combination of two or more.
[0128] Among the above, as the above-mentioned (D) non-fibrous filler, from the viewpoints of dimensional characteristics, sliding characteristics, heat resistance, rigidity, strength, etc., at least one selected from wollastonite, calcium carbonate, talc, kaolin, mica, milled fiber and boron nitride is preferably used.
[0129] The (D) non-fibrous filler is more preferably one or more selected from the group consisting of wollastonite, calcium carbonate, talc, milled fiber and boron nitride, and particularly preferably one or more selected from the group consisting of wollastonite, talc and boron nitride.
[0130] From the viewpoints of dimensional characteristics, sliding characteristics, mechanical properties, etc., the non-fibrous filler (D) preferably has a weight average particle size of 0.01 μm or more and 300 μm or less and / or a weight average major diameter of 0.01 μm or more and 300 μm or less. When the non-fibrous filler (D) has the above particle size or major diameter range, higher characteristics can be exhibited.
[0131] It should be noted that the definition of the above-mentioned (D) non-fibrous filler is not particularly limited as long as it is non-fibrous, and it may be an organic filler and / or an inorganic filler. In addition, the non-fibrous filler has various shapes, including particle, needle, layer, etc.
[0132] The above-mentioned non-fibrous filler may be used alone or in combination of two or more.
[0133] In addition, the weight average particle size and weight average major diameter of the above-mentioned (D) non-fibrous filler can be measured by the following method.
[0134] First, the molded article is dissolved in a solvent such as formic acid that can dissolve the (A) polyamide resin. Next, 100 or more (D) non-fibrous fillers are randomly selected from the obtained insoluble components. Next, the (D) non-fibrous fillers are observed using an optical microscope or a scanning electron microscope, and the weight average particle size or weight average major diameter can be obtained by dividing the total of the measured particle sizes or major diameters by the total weight of the measured (D) non-fibrous fillers.
[0135] In the polyamide composition of the present embodiment, the content of the non-fibrous filler (D) is preferably 0.05 parts by mass or more and 150 parts by mass or less, more preferably 0.1 parts by mass or more and 100 parts by mass or less, and even more preferably 0.5 parts by mass or more and 80 parts by mass or less, relative to 100 parts by mass of the polyamide resin (A).
[0136] When the content of the non-fibrous filler (D) is greater than the lower limit (0.05 parts by mass), the mechanical properties such as strength and rigidity of the molded product and the sliding properties tend to be further improved. On the other hand, when the content of the non-fibrous filler (D) is less than the upper limit (150 parts by mass), a molded product having a better surface appearance and excellent sliding properties tends to be obtained.
[0137] In particular, when the (D) non-fibrous filler is talc and the content of the (D) non-fibrous filler relative to 100 parts by mass of the (A) polyamide resin is within the above range, there is a tendency to obtain a molded product that has a more excellent surface appearance and is particularly less likely to cause wear to the counterpart material in terms of sliding properties.
[0138] (Copper compounds)
[0139] The polyamide resin composition of the present embodiment may also contain a copper compound. Examples of the copper compound include copper halides, copper acetate, copper propionate, copper benzoate, copper adipate, copper terephthalate, copper isophthalate, copper salicylate, copper nicotinate, copper stearate, etc., or copper complex salts obtained by coordination with a chelating agent such as ethylenediamine or ethylenediaminetetraacetic acid, but are not limited thereto.
[0140] These copper compounds may be used alone or in combination of two or more.
[0141] Among these, the copper compound is preferably cuprous iodide, cuprous bromide, cupric bromide, cuprous chloride, and cupric acetate, and more preferably cuprous iodide. In addition, from the viewpoint of sliding properties, the copper compound is preferably used as a masterbatch with a halide of a metal selected from the group consisting of an alkali metal and an alkaline earth metal.
[0142] The content of the copper compound is 0.01 to 5 parts by mass, preferably 0.01 to 4 parts by mass, and more preferably 0.03 to 3 parts by mass, relative to 100 parts by mass of the component (A).
[0143] By setting the amount of the copper compound to be added within the above range, heat aging resistance can be improved, copper precipitation or corrosion can be suppressed, and the friction coefficient or wear depth can be reduced.
[0144] (halide of a metal selected from the group consisting of alkali metals and alkaline earth metals)
[0145] The polyamide resin composition of the present embodiment may further contain a halide of a metal selected from the group consisting of alkali metals and alkaline earth metals (hereinafter, sometimes simply referred to as “metal halide”).
[0146] Examples of the metal halide include potassium iodide, sodium iodide, potassium bromide, potassium chloride, sodium chloride, etc. Among these, potassium iodide is preferred.
[0147] It should be noted that these metal halides may be used alone or in combination of two or more.
[0148] The amount of the metal halide added is 0.05 to 5 parts by mass, preferably 0.1 to 4 parts by mass, and more preferably 0.2 to 3 parts by mass, based on 100 parts by mass of the (A) polyamide resin.
[0149] By setting the amount of the metal halide to be added within the above range, heat aging resistance can be improved, copper precipitation or corrosion can be suppressed, and the friction coefficient or wear depth can be reduced.
[0150] It should be noted that the maximum particle size of the copper compound and the metal halide is preferably 50 μm or less, more preferably 20 μm or less, and further preferably 10 μm or less.
[0151] It should be noted that the above particle size refers to the biaxial average diameter, that is, the average value of the short diameter and the long diameter. Here, the short diameter and the long diameter are respectively the short side and the long side of the circumscribed rectangle with the smallest area circumscribed to the particle. The maximum particle size of the copper compound and the metal halide can be determined by observing at least 50 particles using a scanning electron microscope (SEM).
[0152] By setting the maximum particle size within the above range, the copper compound and the metal halide can be finely dispersed in the polyamide resin (A) even under the condition that the water content in the polyamide resin (A) is low. As a result, metal precipitation and corrosion are suppressed, and the toughness, heat aging resistance, appearance, and color tone of the obtained polyamide resin composition are further improved. In addition, the friction coefficient and wear depth are reduced.
[0153] Furthermore, when the copper compound and the metal halide are prepared into a masterbatch, the molar ratio of halogen to copper (halogen / copper) in the masterbatch is preferably 3-30, more preferably 4-25, and even more preferably 5-23.
[0154] By setting the molar ratio of halogen to copper to above the above lower limit, copper precipitation and metal corrosion can be suppressed. In addition, by setting the molar ratio of halogen to copper to below the above upper limit, corrosion of the screw of the molding machine can be suppressed without damaging mechanical properties such as toughness.
[0155] (Organic compound having at least one amide group)
[0156] The polyamide resin composition of the present embodiment may also contain an organic compound having at least one amide group (but excluding polyamide) in the masterbatch.
[0157] By including an organic compound having at least one amide group (but excluding polyamide), it is possible to prevent the copper compound or metal halide from dissolving in the water in the component (A) to form a complex during melt kneading. In addition, the copper compound or metal halide can be stably dispersed in the component (A) without adversely affecting the component (A), and precipitation or deterioration can be prevented.
[0158] The organic compound having at least one amide group used in the present embodiment is a compound having at least one amide group in a molecular chain. Examples of the organic compound having at least one amide group include, but are not limited to, monoamides, substituted amides, hydroxymethylamides, and bisamides.
[0159] The monoamides are represented by the general formula R-CONH2 (wherein R is a saturated aliphatic group, an unsaturated aliphatic group, an aromatic group having 8 to 30 carbon atoms, or a group in which a part of -H is substituted with -OH).
[0160] Examples of the monoamides include, but are not limited to, lauryl amide, palmitamide, stearyl amide, behenyl amide, hydroxystearyl amide, oleyl amide, erucyl amide, ricinoleyl amide, and the like.
[0161] Substituted amides are of the general formula R 1 -CONH-R 2 represents (where R 1 and R 2 Each independently represents a saturated aliphatic group, an unsaturated aliphatic group, an aromatic group having 8 to 30 carbon atoms, or a group in which a part of -H groups is substituted with -OH).
[0162] Examples of the substituted amides include, but are not limited to, N-lauryl lauramide, N-palmityl palmitamide, N-stearyl stearamide, N-oleyl oleamide, N-stearyl oleamide, N-oleyl stearamide, N-stearyl erucamide, N-oleyl palmitamide, N-stearyl 12-hydroxystearamide, and N-oleyl 12-hydroxystearamide.
[0163] The hydroxymethylamides are represented by the general formula R-CONHCH2OH (wherein R is a saturated aliphatic group, an unsaturated aliphatic group, an aromatic group having 8 to 30 carbon atoms, or a group in which a part of -H is substituted with -OH).
[0164] As a methylolamide, a methylol stearamide, a methylol behenamide, etc. are mentioned, for example.
[0165] Bisamides are composed of the general formula (R-CONH)2(CH2) n represents (wherein R is a saturated aliphatic group, an unsaturated aliphatic group, an aromatic group having 8 to 30 carbon atoms, or a group in which a part of -H is substituted with -OH. n is 1 to 8).
[0166] Examples of the bisamides include, but are not limited to, methylenebislauramide, methylenebishydroxystearamide, ethylenebisoctylamide, ethylenebislauramide, ethylenebisstearamide, ethylenebisisostearamide, ethylenebishydroxystearamide, ethylenebisbehenamide, hexamethylenebisstearamide, hexamethylenebisbehenamide, hexamethylenebishydroxystearamide, butylenebishydroxystearamide, N,N'-distearyl adipamide, N,N'-distearyl sebacamide, methylenebisoleamide, ethylenebisoleamide, ethylenebiserucamide, hexamethylenebisoleamide, N,N'-dioleyl adipamide, N,N'-dioleyl sebacamide, isophthalic acid bisstearamide, and N,N'-distearyl isophthalic acid amide.
[0167] These organic compounds having at least one amide group may be used alone or in combination of two or more.
[0168] Among these, preferred organic compounds having at least one amide group include bisamides.
[0169] The amount of the organic compound having at least one amide group added is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5.0 parts by mass, and even more preferably 1.0 to 4.0 parts by mass, based on 100 parts by mass of the (A) polyamide resin.
[0170] By setting the amount of the organic compound having at least one amide group to be added within the above range, the dispersibility of the copper compound and the metal halide in the component (A) can be improved, and the heat aging resistance can be further improved. As a result, copper precipitation and metal corrosion can be suppressed, and the friction coefficient or wear depth can be reduced.
[0171] The water content of the masterbatch is preferably 0.06% to 1.0% by mass, more preferably 0.10% to 0.75% by mass, and even more preferably 0.15% to 0.75% by mass, relative to the total mass of the masterbatch.
[0172] The water in the masterbatch may be present in the form of water bound to polyamide molecules or may be water attached to the surface of the masterbatch, for example, the surface of masterbatch pellets or masterbatch powder.
[0173] By adjusting the water content within the above range, the aggregation of copper compounds or metal halides can be suppressed. As a result, mechanical properties such as toughness and heat aging resistance can be improved, copper precipitation and metal corrosion can be suppressed, and the friction coefficient and wear depth can be reduced.
[0174] In the polyamide resin composition of the present embodiment, the moisture content of the masterbatch can be adjusted by controlling the degree of decompression in the extruder, the immersion time and length in the strand bath during cooling, or the amount of water sprayed.
[0175] The water content of the polyamide resin composition in the present embodiment is preferably 0.01 to 1% by mass, more preferably 0.03 to 0.5% by mass, and further preferably 0.05 to 0.30% by mass, relative to the total mass of the polyamide resin composition.
[0176] The water in the polyamide resin composition may be present in the form of water bound to the polyamide molecules, or may be water attached to the surface of the polyamide resin composition, such as the surface of particles or powder. From the viewpoint of improving the effect of the present invention, it is more preferably present in the form of water bound to the polyamide molecules.
[0177] By adjusting the water content of the polyamide resin composition to the above range, the aggregation of copper compounds or metal halides can be suppressed. As a result, mechanical properties such as toughness and heat aging resistance can be improved, copper precipitation and metal corrosion can be suppressed, and the friction coefficient and wear depth can be reduced.
[0178] The water content of the polyamide resin composition can be adjusted by controlling the degree of pressure reduction in the extruder, the immersion time and length in the strand bath during cooling, or the amount of water sprayed.
[0179] (Heat stabilizer)
[0180] The polyamide resin composition of the present embodiment may further contain a heat stabilizer. The heat stabilizer also has an effect of improving heat aging resistance and reducing friction coefficient or wear depth.
[0181] The heat stabilizer is not particularly limited, and examples thereof include phenol stabilizers such as hindered phenol compounds, phosphite stabilizers, hindered amine stabilizers, triazine stabilizers, and sulfur-containing stabilizers.
[0182] Among these, hindered phenol compounds are preferably used as phenol stabilizers.
[0183] Examples of the hindered phenol compound include N,N'-hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,4-bis(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylanilino)-1,3,5-triazine, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2-thiophene 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 2,2'-thiobis(4-methyl-6-tert-butylphenol), N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid), diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, calcium bis(ethyl 3,5-di-tert-butyl-4-hydroxybenzylsulfonate), tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, 2 ,6-di-tert-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-tert-butyl-4-ethylphenol, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate stearyl, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), octylated diphenylamine, 2,4-bis[(octylthio)methyl]-o-cresol, 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate isooctyl, 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), 3,9-bis[1,1-dimethyl The invention also includes, but is not limited to, 2-[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, ethylene glycol bis[3,3'-bis(4'-hydroxy-3'-tert-butylphenyl)butyrate, 1,3,5-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)-s-triazine-2,4,6-(1H,3H,5H)trione, d-α-tocopherol, and the like.
[0184] The content of the hindered phenol-based heat stabilizer is preferably 0.01 to 5 parts by mass, more preferably 0.015 to 3 parts by mass, relative to 100 parts by mass of the component (A).
[0185] (Moldability Improver)
[0186] The polyamide resin composition of the present embodiment may further contain a moldability improver as required within a range not impairing the purpose of the present invention.
[0187] The moldability improving agent is not particularly limited, and examples thereof include higher fatty acids, higher fatty acid metal salts, higher fatty acid esters, and higher fatty acid amides.
[0188] Examples of higher fatty acids include, but are not limited to, saturated or unsaturated linear or branched aliphatic monocarboxylic acids having 8 to 40 carbon atoms, such as stearic acid, palmitic acid, behenic acid, erucic acid, oleic acid, lauric acid, and montanic acid.
[0189] Among these, stearic acid and montanic acid are preferred.
[0190] The higher fatty acid metal salt refers to the metal salt of the above-mentioned higher fatty acid.
[0191] The metal element of the metal salt is preferably an element of Group 1, Group 2, or Group 3 of the periodic table, zinc, or aluminum, and more preferably an element of Group 1 or Group 2 such as calcium, sodium, potassium, or magnesium, or aluminum.
[0192] Examples of the higher fatty acid metal salt include, but are not limited to, stearic acid metal salts such as calcium stearate, aluminum stearate, zinc stearate, and magnesium stearate; montanic acid metal salts such as calcium montanate and sodium montanate; and palmitic acid metal salts such as calcium palmitate.
[0193] Among these, montanic acid metal salts and stearic acid metal salts are preferred.
[0194] The higher fatty acid ester refers to an esterification product of the above-mentioned higher fatty acid and alcohol.
[0195] Preferred are esters of aliphatic carboxylic acids having 8 to 40 carbon atoms and aliphatic alcohols having 8 to 40 carbon atoms.
[0196] Examples of the aliphatic alcohol include, but are not limited to, stearyl alcohol, behenyl alcohol, and lauryl alcohol.
[0197] As a higher fatty acid ester, stearyl stearate, behenyl behenate, etc. are mentioned, for example.
[0198] The higher fatty acid amide refers to an amide compound of the above-mentioned higher fatty acid.
[0199] Examples of the higher fatty acid amide include, but are not limited to, stearamide, oleamide, erucamide, ethylenebisstearamide, ethylenebisoleamide, N-stearyl stearamide, and N-stearyl erucamide.
[0200] These higher fatty acids, higher fatty acid metal salts, higher fatty acid esters, and higher fatty acid amides may be used alone or in combination of two or more.
[0201] (Colorant)
[0202] The polyamide resin composition of the present embodiment may further contain a colorant as needed within a range not impairing the purpose of the present invention.
[0203] There are no particular restrictions on the colorant, and examples thereof include dyes such as aniline black; pigments such as titanium oxide and carbon black; metal particles such as aluminum, colored aluminum, nickel, tin, copper, gold, silver, platinum, iron oxide, stainless steel, and titanium; and metal pigments such as mica pearlescent pigments and colored graphite.
[0204] (Other resins)
[0205] The polyamide resin composition of the present embodiment may further contain other resins as necessary within a range not impairing the purpose of the present invention.
[0206] Such a resin is not particularly limited, and examples thereof include thermoplastic resins and rubber components described below.
[0207] Examples of the thermoplastic resin include, but are not limited to, polystyrene-based resins such as atactic polystyrene, isotactic polystyrene, syndiotactic polystyrene, AS (acrylonitrile-styrene) resin, and ABS (acrylonitrile-butadiene-styrene) resin; acrylic resins such as polyacrylic acid, polyacrylate, and polymethyl methacrylate; and halogen-containing vinyl compound-based resins such as polyvinyl chloride and polyvinylidene chloride.
[0208] These thermoplastic resins may be used alone or in combination of two or more.
[0209] Examples of the rubber component include natural rubber, polybutadiene, polyisoprene, polyisobutylene, chloroprene rubber, polysulfide rubber, polysulfide rubber, acrylic rubber, polyurethane rubber, silicone rubber, epichlorohydrin rubber, styrene-butadiene block copolymer (SBR), hydrogenated styrene-butadiene block copolymer (SEB), styrene-butadiene-styrene block copolymer (SBS), hydrogenated styrene-butadiene-styrene block copolymer (SEBS), styrene-isoprene block copolymer (SIR), hydrogenated styrene-isoprene block copolymer (SEP), styrene-isoprene-styrene block copolymer (SIS), hydrogenated styrene-isoprene-styrene block copolymer (SEPS), styrene-butadiene random copolymer, hydrogenated styrene-butadiene random copolymer, and styrene. - Ethylene-propylene random copolymer, styrene-ethylene-butene random copolymer, ethylene-propylene copolymer (EPR), ethylene-(1-butene) copolymer, ethylene-(1-hexene) copolymer, ethylene-(1-octene) copolymer, ethylene-propylene-diene copolymer (EPDM); butadiene-acrylonitrile-styrene core-shell rubber (ABS), methyl methacrylate-butadiene-styrene core-shell rubber (MBS), methyl methacrylate-butyl acrylate-styrene core-shell rubber (MAS), octyl acrylate-butadiene-styrene core-shell rubber (MABS), alkyl acrylate-butadiene-acrylonitrile-styrene core-shell rubber (AABS), butadiene-styrene core-shell rubber (SBR), siloxane-containing core-shell rubber represented by methyl methacrylate-butyl acrylate siloxane, and other core-shell types.
[0210] These rubber components may be used alone or in combination of two or more.
[0211] The polyamide resin composition of the present embodiment is not particularly limited as long as the application requires mechanical properties and sliding properties, and can be widely used as a raw material for sliding parts such as electrical / electronic parts, automobile parts, building parts, and industrial parts. Examples of sliding parts include bearings, gears, door stoppers, chain guide parts, etc., which are usually used as injection molded bodies.
[0212] <Method for producing polyamide resin composition>
[0213] The polyamide resin composition of the present embodiment can be obtained by mixing and kneading (A) a polyamide resin, (B) a polyolefin graft copolymer having an aromatic ring-containing polymer in a side chain, (C) a compatibilizer, (D) a non-fibrous filler, and other components such as a copper compound and a metal halide as required.
[0214] The copper compound and the metal halide are preferably prepared in advance as a master batch, and then melt-kneaded together with the (A) component, the (B) component, and the (C) component. Alternatively, the copper compound, the metal halide, and the (A) component are preferably prepared in advance as a master batch, and then melt-kneaded together with the (B) component and the (C) component.
[0215] When producing the polyamide resin composition, the raw material of the component (C) can be added when the component (A) is mixed and kneaded with a copper compound and metal halide as required and other components, and the composition can be prepared in a twin-screw extruder.
[0216] (Masterbatch preparation process)
[0217] The masterbatch is prepared by melt-kneading the copper compound and the metal halide.
[0218] It is preferred that the above-mentioned organic compound having at least one amide group (excluding polyamide) be added in addition to the above-mentioned copper compound and metal halide.
[0219] It is preferred that the component (A) is blended in addition to the organic compound having at least one amide group (excluding polyamide).
[0220] When the organic compound having at least one amide group (excluding polyamide) and the component (A) are added, the copper compound, the metal halide and the organic compound having at least one amide group (excluding polyamide) may be added to the component (A) separately. Alternatively, at least two of the three compounds may be mixed in advance and added to the component (A), or at least two of the three compounds may be mixed in advance and ground and added to the component (A), or at least two of the three compounds may be mixed in advance, ground and added to the component (A) in tablet form.
[0221] As a method for mixing the compounds, a known method can be used. As a method for mixing the compounds, for example, a method of mixing using any one of a tumbler, a Henschel mixer, a plowshare mixer, a Nauta mixer, and a jet mixer can be mentioned.
[0222] The compound may be pulverized by a known method, for example, by using a hammer mill, knife mill, ball mill, jaw crusher, cone crusher, roller mill, jet mill, stone mill, or the like.
[0223] As a method for making a compound into a tablet, a known method can be used. Examples of the method for making a compound into a tablet include compression granulation, tablet molding, dry extrusion granulation, and melt extrusion granulation.
[0224] As the device for performing melt mixing, there is no particular restriction, and known devices can be used. As the device for performing melt mixing, for example, a single screw or twin screw extruder, a Banbury mixer and a mixing roll melt mixer are preferably used. Among them, a twin screw extruder is preferably used. In addition, a degassing mechanism (vent) device and a side feeder device can be equipped in the device for performing melt mixing.
[0225] The temperature of melt kneading in the present embodiment is preferably in the range of 1°C higher than the melting point or softening point of the component (A) determined by differential scanning calorimetry (DSC) according to JIS K7121 to 310°C, more preferably in the range of 10°C higher than the melting point or softening point of the component (A) to 300°C, and further preferably in the range of 15°C higher than the melting point or softening point of the component (A) to 295°C. In the present embodiment, the temperature of melt kneading refers to the set temperature of the barrel of the extruder. The shear rate in the kneader is preferably about 100 (seconds) -1 ) or more. In addition, the average residence time during kneading is preferably about 0.5 minute to about 15 minutes.
[0226] (Step of Melting and Kneading Masterbatch, Component (A), Component (B), and Component (C))
[0227] The polyamide resin composition of the present embodiment is produced by melt-kneading the masterbatch, the component (A), the component (B) and the component (C). When the component (A) is added to the masterbatch, the polyamide resin composition of the present embodiment is produced by melt-kneading the components (B) and (C) in the masterbatch.
[0228] The copper compound and the metal halide are preferably added in an amount of 0.1 to 100 parts by mass, more preferably 0.1 to 20 parts by mass, based on 100 parts by mass of the (A) polyamide resin.
[0229] By setting the total mass of the copper compound and the metal halide within the above range, the precipitation of metallic copper and metal corrosion in the extruder or molding machine are suppressed, and the stability during processing is improved. As a result, the heat aging resistance can be further improved, the friction coefficient or wear depth can be further reduced, and the change in appearance color caused by water absorption can be further suppressed without reducing the mechanical properties of the product.
[0230] The blending ratio of the component (B) and the component (C) relative to 100 parts by mass of the polyamide resin (A) is as described above.
[0231] The masterbatch, the component (A), the component (B), and the component (C) are melt-kneaded together with other components as required.
[0232] The melt kneading step is preferably carried out using various commonly used extruders such as a single-screw or twin-screw extruder. From the viewpoints of productivity, versatility, etc., it is particularly preferred to use a twin-screw extruder. At this time, although the melt kneading temperature depends on the type of component (A), it is preferably adjusted so that the temperature of the molten resin discharged from the discharge port of the extruder reaches a temperature above the melting point of component (A), component (B) and component (C).
[0233] By adjusting the melt-kneading temperature to the above range, extrusion kneading failure is unlikely to occur, and fine dispersion of the components (B) and (C) can be achieved.
[0234] In the case of a twin-screw extruder, the extruder screw preferably has at least two kneading zones in which kneading disks are combined. The kneading zone is a region that suppresses the molten resin from advancing in the extrusion direction and imparts high shear in order to perform kneading efficiently.
[0235] In the melt-kneading step, the following method is preferred: (A) component, (B) component, (C) component and master batch (copper compound and metal halide) and other components (hindered phenol heat stabilizer, etc.) as required are supplied from the uppermost supply port of the twin-screw extruder, and melt-kneaded in a first kneading zone to obtain a first melt-kneaded product; further, (D) non-fibrous filler is supplied from a side supply port provided on the downstream side of the first kneading zone as required, and the non-melted (D) non-fibrous filler is dispersed in the first melt-kneaded product in a second kneading zone provided on the downstream side of the side supply port.
[0236] It is preferred that the various conditions of the extruder (barrel temperature, screw speed, discharge rate, etc.) be set so that the resin temperature of the polyamide resin composition discharged from the extruder outlet after the melt-kneading step is higher than the crystallization temperature of the (A) component and reaches 280° C. to 400° C. or less. By adjusting the temperature of the polyamide resin composition at the discharge outlet to 280° C. to 400° C. or less, the (A) component, the (B) component, and the (C) component can be further finely dispersed. As a result, a polyamide resin composition having excellent sliding properties and mechanical properties can be obtained.
[0237] The temperature of the polyamide resin composition is preferably measured, for example, by bringing a detection portion of a generally commercially available thermocouple thermometer into direct contact with the molten polyamide resin composition discharged from an outlet of an extruder.
[0238] In order to achieve the temperature of the polyamide resin composition, the temperature of the extruder is preferably set to 280° C. or higher and 400° C. or lower.
[0239] The molded article of the polyamide resin composition according to the present embodiment is obtained by molding the polyamide resin composition.
[0240] There are no particular restrictions on the method for obtaining a molded body, and a known molding method can be used.
[0241] Examples of molding methods include extrusion molding, injection molding, vacuum molding, blow molding, injection compression molding, decorative molding, heterogeneous material molding, gas-assisted injection molding, foam injection molding, low-pressure molding, ultra-thin-wall injection molding (ultra-high-speed injection molding), and in-mold composite molding (insert molding, on-substrate injection molding).
[0242] The setting temperature of the molding machine when molding the polyamide resin composition of the present embodiment is preferably set in the range of 5°C higher than the melting point of the component (A) used to 310°C, more preferably in the range of 10°C higher than the melting point of the component (A) used to 300°C, and further preferably in the range of 15°C higher than the melting point of the component (A) used to 295°C.
[0243] By setting the setting temperature of the molding machine within the above temperature range, the polyamide resin composition can be efficiently kneaded during molding, and the (B) component and the (C) component in the polyamide resin composition can be further finely dispersed.
[0244] The polyamide resin composition of the present invention is not particularly limited as long as it is used for applications requiring mechanical properties and sliding properties, and can be widely used as a raw material for sliding parts such as electrical / electronic parts, automobile parts, building parts, and industrial parts. Examples of sliding parts include common injection molded products such as bearings, gears, door stoppers, chain guides, and roller parts.
[0245] Example
[0246] Hereinafter, the present invention will be described in detail with reference to specific examples and comparative examples, but the present invention is not limited to the following examples.
[0247] [Manufacturing example]
[0248] (Production Example 1) Preparation of polyamide 66
[0249] 15000g of an equimolar salt of adipic acid and hexamethylenediamine and 0.5 mol% of an excess of adipic acid relative to all equimolar salt components were dissolved in 15000g of distilled water to obtain a 50% aqueous solution of the raw monomer. The obtained aqueous solution was added to an autoclave with an internal volume of 40L, and the autoclave was replaced with nitrogen. The aqueous solution was stirred at a temperature of 110°C to 150°C, and water vapor was slowly extracted to concentrate the solution to a concentration of 70% by mass. Then, the internal temperature was raised to 220°C. At this time, the autoclave was pressurized to 1.8MPa. In this state, until the internal temperature reached 270°C, the water vapor was slowly extracted and the pressure was maintained at 1.8MPa while reacting for 1 hour.
[0250] Then, the pressure was reduced to atmospheric pressure in about 1 hour. After reaching atmospheric pressure, the pellets were discharged from the lower nozzle in the form of strands, water-cooled and cut to obtain pellets. The obtained pellets were dried at 90°C for 4 hours in a nitrogen stream. The 98% sulfuric acid relative viscosity of the pellets was 2.71, the melting point was 265°C, and the crystallization temperature was 220°C.
[0251] ((A) Polyamide resin)
[0252] (A-1) Polyamide resin
[0253] (A-2) Polyamide resin: 1200-321, manufactured by Asahi Kasei Corporation
[0254] (A-3) Polyamide resin: 1500-X31, manufactured by Asahi Kasei Corporation
[0255] (A-4) Polyamide resin: 1700-X11, manufactured by Asahi Kasei Corporation
[0256] (A-5) Polyamide resin: 3100-X11, manufactured by Asahi Kasei Corporation
[0257] (A-6) Polyamide resin: Stanyl TW341-J, manufactured by DSM Co., Ltd.
[0258] (A-7) Polyamide resin: SF1013A, manufactured by UBE Co., Ltd.
[0259] (A-8) Polyamide resin (described in Production Example 4)
[0260] ((B) Polyolefin-based graft copolymer having an aromatic ring-containing polymer in a side chain)
[0261] (B-1): MODIPER-A1100, manufactured by NOF Corporation, polyolefin graft copolymer
[0262] (B-2): MODIPER-A1401, manufactured by NOF Corporation, polyolefin graft copolymer
[0263] (B'-1): ENGAGE 8180: manufactured by Dow Chemical Japan Ltd., ethylene-octene copolymer
[0264] ((C) Compatibilizer)
[0265] (C-1-1) APOLHYA LP91: manufactured by Arkema Co., Ltd., polyolefin-polyamide polymer
[0266] (C-1-2) Graft copolymer (described in Preparation Example 3): polystyrene-polyamide polymer
[0267] (C-2-1) FUSABOND N525: manufactured by The Dow Chemical Company, maleic anhydride-modified polyolefin polymer
[0268] (C-2-2) FUSABOND MN493D: manufactured by The Dow Chemical Company, maleic anhydride-modified polyolefin polymer
[0269] (C-2-3) FUSABOND N416: manufactured by The Dow Chemical Company, maleic anhydride-modified polyolefin polymer
[0270] (C-2-4) Tuftec M1943: manufactured by Asahi Kasei Corporation, styrene-based thermoplastic elastomer
[0271] (C-3-1) XIBOND 180: manufactured by Polyscope, styrene-maleic anhydride copolymer
[0272] (C-3-2) XIBOND 120: manufactured by Polyscope, styrene-maleic anhydride copolymer
[0273] (C-3-3) XIBOND 280: manufactured by Polyscope, styrene-maleic anhydride copolymer
[0274] (C-3-4) Maleic anhydride-modified polyphenylene ether (m-PPE) (manufactured by Asahi Kasei Corporation) (molecular weight: 54,000)
[0275] ((D) Non-fibrous filling material)
[0276] (D-1) Talc (Tamura Talc Industry Co., Ltd., trade name "TP-09A", average particle size 9 μm)
[0277] (D-2) Talc (manufactured by Nippon Talc Co., Ltd., trade name "MICRO ACE")
[0278] (D-3) Talc (manufactured by IMERYS, trade name "HARtalc T77")
[0279] (D-4) Wollastonite (manufactured by IMERYS, trade name “M400WC-10012”)
[0280] (D-5) Boron nitride (manufactured by Denka Kagaku Kogyo Co., Ltd., trade name “Denka Boron Nitride SP-2”)
[0281] (D'-1) Glass fiber (manufactured by Nippon Electric Glass Co., Ltd., trade name "ECS03T275H", average fiber diameter 10 μm, cut length 3 mm)
[0282] (Other ingredients)
[0283] Cuprous iodide: Cuprous iodide (I), manufactured by Wako Pure Chemical Industries, Ltd.
[0284] Potassium iodide: Potassium iodide, manufactured by Wako Pure Chemical Industries, Ltd.
[0285] Hindered phenolic heat stabilizer: manufactured by BASF, IRGANOX1098
[0286] Spreader: Sanyo Chemical Industries, Ltd., PEG400
[0287] Azine dyes: Aniline black, manufactured by ORIENT CHEMICAL INDUSTRY CO., LTD., NUBIAN (registered trademark) BLACKTH-807
[0288] (Manufacturing Example 2) Preparation of Masterbatch
[0289] 1.5 parts by mass of a copper compound and 32.5 parts by mass of a 40% by mass aqueous solution of a metal halide were added to 100 parts by mass of the polyamide resin (A-1) obtained in the above (Production Example 1). The mixture was melt-kneaded using a twin-screw extruder (manufactured by Plastics Engineering Research Institute, twin-shaft co-rotating screw type, L / D=60 (D=30φ)) at a screw speed of 100 rpm and a barrel temperature of 280° C., thereby obtaining a masterbatch containing the polyamide resin (A-1), the copper compound and the metal halide.
[0290] (Production Example 3) Preparation of polystyrene-polyamide polymer
[0291] 10 wt % of the compatibilizer (C-3-1) was added to the polyamide resin (A), and melt-kneaded using a twin-screw extruder (manufactured by Plastics Engineering Research Institute, twin-shaft co-rotating screw type, L / D=60 (D=30φ)) at a screw speed of 300 rpm and a barrel temperature of 280° C., thereby obtaining a polystyrene-polyamide polymer containing the polyamide resin (A) and 10 wt % of the compatibilizer (C-3-1).
[0292] (Production Example 4) Preparation of Crystalline Semi-Aromatic Polyamide Resin
[0293] 15 kg of 4T / 6T salt (39 / 61 mol / mol) was loaded into a 50-liter rotary dryer. The rotary dryer was vented to 50 mbar and then filled with nitrogen, and the operation was repeated 5 times. While the reaction water was discharged from the rotary dryer, the mixture was heated to a temperature of 220°C for 5 hours and then heated to 255°C for 15 hours. A low nitrogen purge was used during the reaction. The mixture was cooled to 235°C for 19 hours, and then a mixture of 650 g of 1,6-hexamethylenediamine, 300 g of 1,4-butanediamine and 1.0 kg of water was added for 7 hours while the temperature was maintained at 235°C. The mixture was then reacted at 235°C for 29 hours. Next, a nitrogen gas flow was increased and the material was cooled to room temperature. A white powder was obtained.
[0294] [Example 1]
[0295] (A-1) polyamide resin, (B-1) polyolefin graft copolymer, and (C-1-1) compatibilizer were mixed in the amounts listed in Table 1 and supplied from the uppermost supply port of a twin-screw extruder (manufactured by Coperion Corporation, trade name "ZSK26MC18") having a screw diameter of 26 mm. Next, the barrel temperature of the extruder was set to 290° C., and while melt kneading was performed at a screw speed of 300 rpm, (D-1) non-fibrous filler was supplied and extruded from a side supply port provided on the downstream side of the uppermost supply port, to obtain pellets of a polyamide resin composition at a discharge rate of 25 kg / hour.
[0296] The obtained polyamide resin composition pellets were injected into the mold using an injection molding machine NEX50IV-5EG (manufactured by Nissei Plastics Co., Ltd., with a screw diameter of 26 mm and an injection volume of 49 cm 3 ), set the injection + holding time to 25 seconds, cooling time to 15 seconds, mold temperature to 80°C, barrel temperature = (the same as the barrel temperature of the extruder), and mold a multi-purpose test piece A-shaped test piece according to ISO 3167.
[0297] [Examples 2 to 5]
[0298] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Example 1 except that the amount of the compatibilizer (C-1-1) added was increased as shown in Table 1.
[0299] [Example 6]
[0300] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Example 5 except that the amount of the (B-1) polyolefin graft copolymer added was increased as shown in Table 1.
[0301] [Example 7]
[0302] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Example 2 except that the polyolefin graft copolymer (B-2) was added instead of the polyolefin graft copolymer (B-1).
[0303] [Example 8]
[0304] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Example 2 except that the compatibilizer (C-1-2) was added instead of the compatibilizer (C-1-1).
[0305] [Examples 9 to 13]
[0306] Pellets and test pieces of polyamide resin compositions were prepared in the same manner as in Example 2 except that (D-2) to (D-5) non-fibrous fillers were added instead of (D-1) non-fibrous filler as shown in Table 2.
[0307] [Example 14]
[0308] Pellets and test pieces of polyamide resin compositions were prepared in the same manner as in Example 3 except that (A-2) polyamide resins were blended instead of (A-1) polyamide resins as shown in Table 2.
[0309] [Example 15]
[0310] As shown in Table 3, (A-3) polyamide resin was added instead of (A-1) polyamide resin and supplied from the uppermost supply port of a twin-screw extruder having a screw diameter of 26 mm (manufactured by Coperion Corporation, trade name "ZSK26MC18"). Then, the barrel temperature of the extruder was set to 300° C., and while melt kneading was performed at a screw speed of 300 rpm, (D-1) non-fibrous filler was supplied and extruded from a side supply port provided on the downstream side of the uppermost supply port to obtain pellets of a polyamide resin composition at a discharge rate of 20 kg / hour. Except for this, pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1.
[0311] [Example 16]
[0312] As shown in Table 3, (A-4) polyamide resin was added instead of (A-1) polyamide resin and supplied from the uppermost supply port of a twin-screw extruder having a screw diameter of 26 mm (manufactured by Coperion Corporation, trade name "ZSK26MC18"). Subsequently, the barrel temperature of the extruder was set to 310° C., and while melt kneading was performed at a screw speed of 300 rpm, (D-1) non-fibrous filler was supplied and extruded from a side supply port provided on the downstream side of the uppermost supply port to obtain pellets of a polyamide resin composition at a discharge rate of 25 kg / hour. Except for this, pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1.
[0313] [Example 17]
[0314] As shown in Table 3, (A-5) polyamide resin was added instead of (A-1) polyamide resin and supplied from the uppermost supply port of a twin-screw extruder having a screw diameter of 26 mm (manufactured by Coperion Corporation, trade name "ZSK26MC18"). Subsequently, the barrel temperature of the extruder was set to 340°C, and while melt kneading was performed at a screw speed of 300 rpm, (D-1) non-fibrous filler was supplied and extruded from a side supply port provided on the downstream side of the uppermost supply port to obtain pellets of a polyamide resin composition at a discharge rate of 25 kg / hour. Except for this, pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1.
[0315] [Example 18]
[0316] As shown in Table 3, in addition to the polyamide resin (A-1), 43 parts by mass of the polyamide resin (A-5) was added and supplied from the uppermost supply port of a twin-screw extruder having a screw diameter of 26 mm (manufactured by Coperion Corporation, trade name "ZSK26MC18"). Subsequently, the barrel temperature of the extruder was set to 320° C., and while melt kneading was performed at a screw speed of 300 rpm, the non-fibrous filler (D-1) was supplied and extruded from a side supply port provided on the downstream side of the uppermost supply port to obtain pellets of a polyamide resin composition at a discharge rate of 25 kg / hour. Except for this, pellets and test pieces of the polyamide resin composition were prepared in the same manner as in Example 1.
[0317] [Example 19]
[0318] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Example 2 except that (C-2-1) a compatibilizer was added instead of (C-1-1) a compatibilizer as shown in Table 3.
[0319] [Example 20]
[0320] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Example 2 except that (C-2-2) a compatibilizer was added instead of (C-1-1) a compatibilizer as shown in Table 3.
[0321] [Example 21]
[0322] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Example 2 except that (C-2-3) a compatibilizer was added instead of (C-1-1) a compatibilizer as shown in Table 3.
[0323] [Example 22]
[0324] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Example 2 except that (C-2-4) a compatibilizer was added instead of (C-1-1) a compatibilizer as shown in Table 4.
[0325] [Example 23]
[0326] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Example 2, except that the amount of the polyolefin graft copolymer (B-1) was reduced as shown in Table 4, and the compatibilizer (C-2-3) was added instead of the compatibilizer (C-1-1) and the amount of the compatibilizer was increased as shown in Table 4.
[0327] [Example 24]
[0328] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Example 23 except that the amount of the polyolefin graft copolymer (B-1) was reduced and the amount of the compatibilizer (C-2-3) was increased as shown in Table 4.
[0329] [Example 25]
[0330] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Example 1 except that (C-3-1) compatibilizer was added instead of (C-1-1) compatibilizer as shown in Table 4 and the amount of compatibilizer was increased as shown in Table 4.
[0331] [Example 26]
[0332] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Example 1 except that (C-3-2) compatibilizer was added instead of (C-1-1) compatibilizer as shown in Table 4 and the amount of compatibilizer was increased as shown in Table 4.
[0333] [Example 27]
[0334] In addition to the (A-1) polyamide resin, the (B-1) polyolefin graft copolymer and the (C-1-1) compatibilizer, 2 parts by mass of the masterbatch obtained in the above (Production Example 2) was added as a copper compound and a metal halide, and pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Example 5.
[0335] [Comparative Examples 1 to 3]
[0336] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Example 1 except that (C) a compatibilizer was not blended and (B-1) a polyolefin graft copolymer and (D) a non-fibrous filler were blended as shown in Table 5.
[0337] [Comparative Example 4]
[0338] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Example 1 except that the (B) polyolefin graft copolymer and the (C) compatibilizer were not formulated and the (D-1) non-fibrous filler was formulated as shown in Table 5.
[0339] [Comparative Example 5]
[0340] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Comparative Example 2 except that the component (B'-1) was added instead of the (B) polyolefin graft copolymer and the amount of the (D) non-fibrous filler was reduced as shown in Table 5.
[0341] [Comparative Example 6]
[0342] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Comparative Example 2 except that the component (B′-1) was added instead of the (B) polyolefin graft copolymer and the (C) compatibilizer was further added as shown in Table 5.
[0343] [Comparative Example 7]
[0344] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Comparative Example 6 except that the (B) polyolefin graft copolymer was not blended and the amount of the (C-1-1) compatibilizer was increased as shown in Table 5.
[0345] [Comparative Example 8]
[0346] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Comparative Example 7 except that the compatibilizer (C-3-2) was added instead of the compatibilizer (C-1-1) and the amount of the compatibilizer was reduced as shown in Table 6.
[0347] [Comparative Example 9]
[0348] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Comparative Example 7 except that the compatibilizer (C-2-4) was added instead of the compatibilizer (C-1-1).
[0349] [Comparative Example 10]
[0350] Pellets and test pieces of a polyamide resin composition were prepared in the same manner as in Comparative Example 7 except that the compatibilizer (C-1-1) was not added.
[0351] <Evaluation>
[0352] The following evaluations were performed using the test pieces prepared in the respective Examples and Comparative Examples.
[0353] (Reciprocating sliding test)
[0354] Using the multi-purpose test piece A-shaped test piece obtained in the examples and comparative examples, a pin-on-disc friction and wear tester (TRB3 model manufactured by Anton Paar) was used, and a SUS304 test piece (6.5 mm diameter ball) was used as the target material. A sliding test was carried out under the conditions of a linear speed of 50 mm / sec, a reciprocating distance of 20 mm, a temperature of 23°C, and a humidity of 50%. In addition, a friction coefficient test was carried out under the conditions of a load of 4 kg and a reciprocating number of 10,000 times. In addition, the maximum wear depth (μm) of the wear scar of the sample after the sliding test was measured using a surface roughness meter (575A-30 manufactured by Toyo Seimitsu Co., Ltd.).
[0355] The friction coefficient and wear depth were measured by the above test, and the results are shown in Table 1.
[0356] In the evaluation of the wear of the counterpart material, the surface (sliding surface) of the SUS304 test piece of the counterpart material after the reciprocating sliding test was observed using a digital microscope (VHX-5000 manufactured by KEYENCE Corporation) at a magnification of 20. The observation results of the counterpart material were evaluated on a scale of 1 to 5 as shown in Table 1.
[0357] 1: Large chipping is observed on the object material.
[0358] 2: Chipping is observed on the target material.
[0359] 3: Some chipping was observed on the target material.
[0360] 4: Slight chipping was observed on the object material.
[0361] 5: Almost no chipping is observed on the target material.
[0362] (Critical PV test)
[0363] Using the multi-purpose test piece A-shaped test piece obtained in the examples and comparative examples, a friction and wear tester (EFM-III-F manufactured by A&D Co., Ltd.) was used, and a S45C ring (surface roughness of 0.8μmRa / contact area of about 2 square centimeters) was used as the object material. A sliding test was carried out under the conditions of a rotation speed of 0.5m / second, a temperature of 23°C, and a humidity of 50%. The test was started with an initial load of 40N, and then increased by 50N each time every 10 minutes. A 30mm long and wide × 2mm thick flat plate was used as the test piece. The critical point at which the melting or wear amount of the sample increased through the above test and the flat plate of the test piece was cut off by 1.5mm was calculated as the critical PV value (kPa·m / s). Then, the obtained critical PV value was evaluated at levels 1 to 5 as shown below, and the results are shown in Table 1.
[0364] 1: less than 600 kPa·m / s;
[0365] 2: greater than or equal to 600 kPa·m / s and less than 800 kPa·m / s;
[0366] 3: greater than or equal to 800 kPa·m / s and less than 1000 kPa·m / s;
[0367] 4: greater than or equal to 1000 kPa·m / s and less than 1200 kPa·m / s;
[0368] 5: 1200 kPa·m / s or more.
[0369] (Tensile test)
[0370] The multipurpose test pieces A-shaped test pieces obtained in Examples and Comparative Examples were used to perform a tensile test at a test speed of 50 mm / min in accordance with ISO 527, and the tensile strength (N / mm) was measured. The measurement results are shown in Table 1.
[0371] In addition, the ratio of the displacement amount of the distance between the clips at the time of fracture to the distance between the clips before the test was defined as the tensile elongation (%).
[0372] Tensile elongation (%) = 100 × displacement at breaking point (mm) / initial distance between fixtures (mm)
[0373] The value obtained by dividing the tensile strength by the tensile elongation was calculated as the tensile elastic modulus (MPa).
[0374] Tensile modulus = tensile strength / tensile elongation
[0375] (Charpy impact strength)
[0376] The multi-purpose test pieces A-shaped test pieces obtained in the examples and comparative examples were processed into 80 mm×10 mm×4 mm, and the notched Charpy impact strength (kJ / m 2 ).
[0377] (Molding shrinkage)
[0378] The pellets of the polyamide resin compositions obtained in the examples and comparative examples were prepared using an injection molding machine NEX50IV-5EG (manufactured by Nissei Plastics Co., Ltd., screw diameter 26 mm, injection volume 49 cm 3 ), set the injection + holding time to 25 seconds (injection pressure 150MPa, injection speed 30mm / sec, holding pressure = 40% of VP switching pressure), cooling time 15 seconds, mold temperature 80℃, barrel temperature = (melting point of polyamide resin + 30)℃, and mold a 60×60×2mmt (ISO294-3 type D2) flat plate molded body according to ISO294-4.
[0379] Then, the MD (flow direction) and TD (vertical direction) of the obtained flat plate molded body were measured, and the ratio of MD to TD (MD / TD) was calculated and evaluated on a scale of 1 to 5 as shown below.
[0380] 5: 0.85≤MD / TD≤1.15
[0381] 4: 0.80≤MD / TD<0.85 or 1.15<MD / TD≤1.20
[0382] 3: 0.70≤MD / TD<0.80 or 1.20<MD / TD≤1.30
[0383] 2: 0.60≤MD / TD<0.70 or 1.30<MD / TD≤1.40
[0384] 1: MD / TD<0.60 or 1.40<MD / TD
[0385] [Table 1]
[0386]
[0387] [Table 2]
[0388]
[0389] [Table 3]
[0390]
[0391] [Table 4]
[0392]
[0393] [Table 5]
[0394]
[0395] [Table 6]
[0396]
[0397] As can be seen from the results in Tables 1 to 6, the polyamide resin compositions of each example are all excellent in dimensional properties, sliding properties (friction coefficient, wear depth, counterpart wear, critical PV value), and mechanical properties (tensile strength, elastic modulus). In particular, it can be clearly confirmed that by combining the (B) component with the (C) component and the (D) component, in particular, the dimensional properties (MD / TD ratio close to 1) and sliding properties are excellent. In addition, as can be seen from the results in Examples 14 to 18, by combining the (B) component with the (C) component and the (D) component, the sliding properties and mechanical properties are all excellent without being limited by the type of the (A) polyamide resin. In addition, as can be seen from the results in Examples 9 to 13 and 19 to 26, by combining the (B) component with the (C) component and the (D) component, the dimensional properties, sliding properties, and mechanical properties are excellent through various combinations without limiting each component and relying on one.
[0398] On the other hand, according to the results of Tables 1 to 6, although some comparative polyamide resin compositions with excellent properties were obtained, the results failed to achieve both dimensional properties and sliding properties. In particular, the sliding properties were significantly inferior to those of the examples.
[0399] Industrial Applicability
[0400] The polyamide resin composition of the present invention has excellent sliding characteristics and mechanical properties, and therefore has practical application in the automotive field, electrical and electronic field, mechanical and industrial field, office equipment field, aviation and aerospace field, etc. In addition, by combining the component (B), the component (C) and the component (D), the performance of each component can be exerted without being limited to one type. A wider range of combinations can be made, and it has wide industrial applicability.
Claims
1. A polyamide resin composition, characterized in that The polyamide resin composition comprises: (A) Polyamide resin, (B) a polyolefin graft copolymer having an aromatic ring-containing polymer in a side chain, (C) Compatibilizer, and (D) Non-fibrous filling materials.
2. The polyamide resin composition according to claim 1, characterized in that The (C) compatibilizer has an olefin skeleton and / or an aromatic ring skeleton.
3. The polyamide resin composition according to claim 1 or 2, characterized in that The content of the polyolefin graft copolymer (B) is 1 to 15 parts by mass relative to 100 parts by mass of the polyamide resin (A). The content of the (C) compatibilizer is 0.01 to 15 parts by mass relative to 100 parts by mass of the (A) polyamide resin. The content of the (D) non-fibrous filler is 1 to 150 parts by mass based on 100 parts by mass of the (A) polyamide resin.
4. The polyamide resin composition according to claim 1 or 2, characterized in that The (C) compatibilizer has affinity with the olefin skeleton.
5. The polyamide resin composition according to claim 1 or 2, characterized in that: The (C) compatibilizer has an affinity for aromatic rings.
6. The polyamide resin composition according to claim 1 or 2, characterized in that: The (C) compatibilizer has a reactive functional group that reacts with the (A) polyamide resin.
7. The polyamide resin composition according to claim 1 or 2, characterized in that: The (B) polyolefin-based graft copolymer has polyethylene in its main chain.
8. The polyamide resin composition according to claim 1 or 2, characterized in that: The (C) compatibilizer includes a structural unit derived from a carboxylic acid anhydride.
9. The polyamide resin composition according to claim 1 or 2, characterized in that: The (D) non-fibrous filler has a weight average particle size and / or a weight average major diameter of 0.01 μm or more and 300 μm or less.
10. The polyamide resin composition according to claim 1 or 2, characterized in that: The (C) compatibilizer has an amide bond in a side chain.
11. A method for producing a polyamide resin composition, characterized in that: (A) a polyamide resin, (B) a polyolefin-based graft copolymer having an aromatic ring-containing polymer in a side chain, and (C) a compatibilizer are melt-kneaded.
12. A molded body, characterized in that: The molded article is obtained by molding the polyamide resin composition according to claim 1 or 2.
13. A sliding member, characterized in that: The sliding member comprises the polyamide resin composition according to claim 1 or 2.
Citation Information
Patent Citations
Slide member for power transmission guide
JP2011084679A
Polyamide resin composition, its molding, and method for using the same
JP2012102189A
Polyamide resin composition and resin molded article thereof
JP2016117842A
Resin composition and sliding member using same
WO2013047625A1